FILSAFAT PERENNIAL DAN PLURALISME AGAMA - Suhermanto Ja'far (JURNAL AT-TURAS, 2015)
This study is to explore religious pluralism and pherennial philosophy. Some of conclusions are drawn. Firstly, the pherennial philosophy is a tradition forming intellectual heritage and human spirituality which is originally and directly delivered from the sacred revelation. Secondly, religion is institutionalization of pious experience to God, as the religion is manifestation of an organized pious system. Due to the fact, as an institution, religion continously develops in the certain context and situation. It means that religion could be contextually and situationally different depending on the followers’ personal faith and belief. Thirdly, Indonesia is a unique state with heterogeneous aspects in religion, language, ethnicity, and others, but these different aspects are united in the single ideology of Bhinneka Tunggal Ika firstly coined by Mpu Tantular in Kitab Sutasoma.